vault backup: 2025-02-18 09:56:11
This commit is contained in:
parent
0eeea19351
commit
38e1b487ec
27
.obsidian/plugins/obsidian-git/data.json
vendored
27
.obsidian/plugins/obsidian-git/data.json
vendored
@ -1,27 +0,0 @@
|
|||||||
{
|
|
||||||
"commitMessage": "vault backup: {{date}}",
|
|
||||||
"autoCommitMessage": "vault backup: {{date}}",
|
|
||||||
"commitDateFormat": "YYYY-MM-DD HH:mm:ss",
|
|
||||||
"autoSaveInterval": 5,
|
|
||||||
"autoPushInterval": 0,
|
|
||||||
"autoPullInterval": 5,
|
|
||||||
"autoPullOnBoot": true,
|
|
||||||
"disablePush": false,
|
|
||||||
"pullBeforePush": true,
|
|
||||||
"disablePopups": false,
|
|
||||||
"listChangedFilesInMessageBody": false,
|
|
||||||
"showStatusBar": true,
|
|
||||||
"updateSubmodules": false,
|
|
||||||
"syncMethod": "merge",
|
|
||||||
"customMessageOnAutoBackup": false,
|
|
||||||
"autoBackupAfterFileChange": false,
|
|
||||||
"treeStructure": false,
|
|
||||||
"refreshSourceControl": true,
|
|
||||||
"basePath": "",
|
|
||||||
"differentIntervalCommitAndPush": false,
|
|
||||||
"changedFilesInStatusBar": false,
|
|
||||||
"showedMobileNotice": true,
|
|
||||||
"refreshSourceControlTimer": 7000,
|
|
||||||
"showBranchStatusBar": true,
|
|
||||||
"setLastSaveToLastCommit": false
|
|
||||||
}
|
|
@ -139,19 +139,28 @@ This is used when you want to take the derivative of a function raised to a func
|
|||||||
|
|
||||||
1. $\dfrac{d}{dx} x^x$
|
1. $\dfrac{d}{dx} x^x$
|
||||||
2. $y = x^x$
|
2. $y = x^x$
|
||||||
3. $\ln y = \ln x^x$
|
3. Take the natural log of both sides: $\ln y = \ln x^x$
|
||||||
4. $\ln(y) = x*\ln(x)$
|
4. $\ln(y) = x*\ln(x)$
|
||||||
5. $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$
|
5. Use implicit differentiation: $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$
|
||||||
6. $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$
|
6. Solve for $\dfrac{dy}{dx}$: $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$
|
||||||
|
7. $\dfrac{dy}{dx} = (\ln x + 1) * y$
|
||||||
|
8. Referring back to step 2, $y = x^x$, so the final form is:
|
||||||
|
9. $\dfrac{dy}{dx} = (\ln(x) + 1)x^x$
|
||||||
|
|
||||||
|
### Examples
|
||||||
|
> Find the derivative of the function $y = (2x \sin x)^{3x}$
|
||||||
|
|
||||||
|
1. $\ln y = \ln (3x \sin x)^{3x}$
|
||||||
|
2. $\ln y = 3x * ln(2x \sin x)$*
|
||||||
# Chain Rule
|
# Chain Rule
|
||||||
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
||||||
## Examples
|
## Examples
|
||||||
> Given the function $(x^2+3)^4$, find the derivative.
|
> Given the function $(x^2+3)^4$, find the derivative.
|
||||||
|
|
||||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||||
7. First find the derivative of the outside function function ($f(x) = x^4$):
|
3. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||||
8. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
4. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||||
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||||
> Apply the chain rule to $x^4$
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
@ -187,7 +196,7 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||||
|
|
||||||
Given these facts:
|
Given these facts:
|
||||||
9. Let $y$ be some function of $x$
|
5. Let $y$ be some function of $x$
|
||||||
10. $\dfrac{d}{dx} x = 1$
|
6. $\dfrac{d}{dx} x = 1$
|
||||||
11. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
7. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||||
|
|
||||||
|
Loading…
x
Reference in New Issue
Block a user